Features interference electromyogram rectus femoris for skilled players in the context of special exercises - Sirenko, P. O.; Korolinska, S. V.; Sirenko Y. P. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
The problems of improving physical fitness skilled players. The aim of the study is to determine the optimal position of the hip angle to the vertical plane for the manifestation of a maximum of bioelectric activity of the rectus femoris. In the experiment involved 15 players of FC "Metalist" (age 18 - 30 years). Has electromyogram muscle activity "hip flexion standing" on the mechanical simulator. Athletes performed around the maximum contraction of the muscle (musculus rectus femoris) for 5 seconds. Found that the angle of 70 degrees has minimal background for developing muscular force. It is established that the position of the straight leg on the same vertical axis with the body is the position of the largest overlap actinomyosinic filaments in muscle sarcomere.